PEMANFAATAN Azolla sp FERMENTASI SEBAGAI BAHAN PAKAN AYAM LOKAL PEDAGING UNGGUL (ALPU) - Muhammad - Daud; M. Aman Yaman; - Zulfan; Yunasri Usman (Udayana University, 2022)
This research aimed to examine the use of Azolla sp as a feed ingredients for superior local chicken(ALPU) and and its effect on the growth and carcass production. A hundred ALPU day old chicks (DOC) usedin this experiment and raised until the age of 10 weeks. The method was experimental, using a completelyrandomized design (CRD) consisting of 4 ration treatments and 5 replications (5 birds/replication). Thetreatment rations used were R1 (100% commercial feed/control), R2 (95% commercial feed+5% fermented Azolla sp), R3 (90% commercial feed+10% fermented Azolla sp), and R4 (85% commercial feed+15% fermented Azolla sp). Variables observed included feed consumption, body weight gain, feed conversion, final body weight, carcass weight, carcass cut weight, carcass percentage, and carcass cut percentage. The results showed that the use of fermented Azolla sp as feed ingredients for ALPU around 5-15% in mixed commercial feed did not significantly affect the growth and carcass production of 10-week-old ALPU chickens. It was concluded that fermented Azolla sp can be used as feed ingredients for ALPU up to 15% in mixed commercial feed without affecting the growth and carcass production. Keyword: ALPU, Azolla sp, carcass, fermented, performance